RUMAH UMKM INDUSTRI KREATIF PEMBUATAN PAKET PRODUK SANGKAR BURUNG DENGAN MEMANFAATKAN LIMBAH MEBEL DAN KAIN PERCA - Nughthoh Arfawi Kurdhi; Nugroho Arif Sudibyo; Fanny Widadie; Dewi Retno Sari S (Universitas Mataram, 2022)
The creative industry is one of the solutions to the COVID-19 pandemic. The creative industry can adapt to changing times. MSME partners have problems in production, management, and marketing. The purpose of this service activity is to create industry products that are expected to become creative industry products that can compete. The method used is the 4P technique, the stages of implementation are observation, implementation, training, and mentoring. This community service activity took place in Ngemplak District, Boyolali Regency, Central Java Province. The partner mentoring process was carried out in Pandeyan Village for MSMEs Martha Mebel while Mukti Jaya's MSMEs took place in Gagaksipat Village. The training process for using the POS system is located in Gagaksipat Village where one of the community service members is located. During the training, he was also accompanied by students from the Mathematics Study Program, FMIPA UNS. The results of the training activities that have been carried out are that the training participants can operate the POS system. In this dedication activity, there was quite intense interaction between the participants and the presenters. At the end of this activity, participants can operate the POS system that has been developed. Participants can enter item and category data, besides that participants can make sales transactions and sales reports. The suggestion from this service activity is that there is support for devices and the internet that supports being able to access and edit the POS system that has been made.